The Generalized Coefficients of Earth Pressure: Numerical Validation and Comparison with Eurocode 8-5 Method - Pantelidis, Lysandros; Christodoulou, Panagiotis; Assefa, Eleyas; Sachpazis, Costas (My University, 2024)
The first author recently offered a unified continuum mechanics approach for deriving earth pressure coefficients for any soil state between the “at rest” state and the active or passive state, applicable to cohesive-frictional soils and both horizontal and vertical pseudo-static conditions. It is worth noticing that under static conditions, this relatively complicated analysis based on Cauchy's first law of motion, which has been extended suitably to deformable bodies with internal resistance, leads to the well-known Rankine's expression for cohesive-frictional soils for the active state. In the same paper, an analytical expression for calculating the required wall movement for the mobilization of the active (or passive) state is also presented. The validity of the above-mentioned analytical expressions is examined herein through several application examples, comparing the analytical results with the respective finite element analysis results. The comparison showed that the proposed expressions are excellent tools for calculating earth pressures and displacements. The results were also compared against the respective ones obtained using EN 1998-5:2004 and the prEN 1998-5 (2021 draft standard). The comparison shows that both Eurocode 8-5 versions’ return values that significantly deviate from the respective finite element analysis.
Keywords: Active earth pressure; EN 1998-5; Eurocode 8-5; Numerical validation; Passive earth pressure; The generalized coefficients of earth pressure